(untitled) (Research, Society and Development, 2022)
To demonstrate the importance of physical therapy in the prevention process and in the treatment of the elderly in vestibular rehabilitation. Vertigo can be caused by numerous sensory factors; an investigation is needed initially. In the aging process, physiotherapy is essential and a great ally in the life of the elderly, seeking to make them feel confident when performing their routine activities. Sensory disorders can manifest at any stage of life, but the elderly are much more likely to suffer from these disorders. This is a literature review analyzing several studies related to vestibular rehabilitation accessed through data published between 2001 to 2022, and 21 articles were selected. In addition to the physical therapist, the family is very important in the rehabilitation process of the elderly, as it acts as a support where the physical therapist will seek their information, guide and help to draw up an adequate treatment plan, which increases their functional capacity by supporting their independence, improving balance, bringing more security and well-being.